Construction and characterization of the hybrid bacteriophage lambda Charon vectors for DNA cloning. - Williams, B G (1979)
Twenty hybrid lambda phages especially designed for molecular cloning have been constructed and named Charon phages. These phages differ in the ranges of sizes of DNA fragments that may be inserted, by the selections and screens which may be used to isolate and detect the incorporation of cloned fragments, by the way transcription of the cloned fragment may be controlled, by the different restriction enzymes that can be used for cloning, by the phage immunities that may be employed for controlling replication and transcription, and by the biological safety features that they contain. The crosses used to produce the vectors are described, and their genealogy is discussed. The structure of each vector has been verified by genetic tests, by DNA length determinations, by electron micrographic analysis of DNA heteroduplexes, and by gel electrophoresis of restriction enzyme digests. In the course of these constructions, a new EcoRI site was found in a derivative of lambda Aam32Bam1 which maps very near the left cohesive end of lambda.